Evaluation of cranial base repair techniques utilizing a novel cadaveric CPAP model. Issue 7 (12th February 2019) - Chitguppi, Chandala; Rimmer, Ryan A.; Garcia, Hermes G.; Koszewski, Ian J.; Fastenberg, Judd H.; Nyquist, Gurston G.; Rosen, Marc R.; Huntley, Colin; Rabinowitz, Mindy R.; Evans, James J.
Abstract : Background: Although recent guidelines for obstructive sleep apnea recommend early postoperative use of continuous positive airway pressure (CPAP) after endonasal skull base surgery, the time of initiation of CPAP is unclear. In this study we used a novel, previously validated cadaveric model to analyze the pressures delivered to the cranial base and evaluate the effectiveness of various repair techniques to withstand positive pressure. Methods: Skull base defects were surgically created in 3 fresh human cadaver heads and repaired using 3 commonly used repair techniques: (1) Surgicel™ onlay; (2) dural substitute underlay with dural sealant onlay; and (3) dural substitute underlay with nasoseptal flap onlay with dural sealant. Pressure microsensors were placed in the sphenoid sinus and sella, both proximal and distal to the repair, respectively. The effectiveness of each repair technique against various CPAP pressure settings (5‐20 cm H2 O) was analyzed. Results: Approximately 79%‐95% of positive pressure administered reached the sphenoid sinus. Sellar pressure levels varied significantly across the 3 repair techniques and were lowest after the third technique. "Breach" points (CPAP settings at which sellar repair was violated) were lowest for the first group. All 3 specimens showed a breach after the first repair technique. For the second repair technique, only a single breach was created in 1 specimen at 20 cm H2 O. No breaches were created in the third group. Conclusion: Different skull base repair techniques have varying ability to withstand CPAP. Both second and third repair techniques performed in a nearly similar fashion with regard to their ability to withstand positive pressure ventilation.